Inhibition of the IRE1/JNK pathway in renal tubular epithelial cells attenuates ferroptosis in acute kidney injury - Liang, Yan; Liu, Zhenjie; Qu, Lingyun; Wang, Yingzi; Zhou, Yali; Liang, Lulu; Guo, Yanhong; Tang, Lin (Frontiers in Pharmacology, 2022)
Backgroud: Ferroptosis is a form of regulated cell death in ischemia-reperfusion (I/R) injury models. Acute kidney injury (AKI) induced by I/R injury can result in cell death, and subcellular structural changes, including expansion of the endoplasmic reticulum (ER), mitochondrial shrinkage, and other morphological changes. Inositol requiring enzyme 1 (IRE1) a proximal ER stress sensor, activates c-Jun NH2-terminal kinases (JNK) in response to ER stress, which is inextricably linked to ER. Method: To determine the resulting damage and relationship between ferroptosis and the IRE1/JNK pathway in AKI, we modeled AKI in I/R renal injury mice and hypoxia/reoxygenation (H/R) HK-2 cells, as in vivo and in vitro experiments, respectively. Results: In I/R renal injury mice, we found that abnormal renal function; damage of renal tubular epithelial cells; activation of the IRE1/JNK pathway and ferroptosis. Our in vitro study showed a large number of reactive oxygen species and more ferroptotic mitochondria in H/R HK-2 cells. By inhibiting IRE1/JNK in I/R renal injury mice, we observed decreased blood urea nitrogen, creatinine, and tissue injury, compared with the I/R group, we also found the markers of ferroptosis changed, including decreased 4-hydroxynonenal and increased glutathione peroxidase 4 , as well as in H/R induced IRE1/JNK knock-down HK-2 cell lines (stable depletion). Furthermore, inhibition of ferroptosis could also attenuate the IRE1/JNK pathway in mice following I/R and HK-2 cells following H/R. Conclusion: We observed cross-talk between the IRE1/JNK pathway and ferroptosis in I/R or H/R induced AKI. Our findings suggest that ferroptosis plays an important role in I/R induced AKI, and that inhibition of the IRE1/JNK pathway can protect against I/R induced renal injury by inhibiting ferroptosis. The inhibition of the IRE1/JNK pathway could therefore be a feasible therapeutic target for treatment of AKI.